Typological characterisation of kilns in north Western gaul in The Roman period - Lecluse, Loes (Rei Cretariae Romanae Fautorum Acta, 2012)
In the region of north West Gaul in most cases only residues of the lower part of Roman kilns were recovered, but in some cases also remains from upper parts have been found.